PERANCANGAN BRANDING DESA WISATA RAJEK WETAN, KELURAHAN TIRTOADI, KECAMATAN MLATI, KABUPATEN SLEMAN YOGYAKARTA - Sudjadi Tjipto Rahardjo (DHARMA BAKTI, 2020)
Rajek Wetan Tourism Village is a village located at Tirtoadi, Mlati, Sleman Regency, Yogyakarta. As one of the pioneer of the tourism village destination, it has a fundamental problem: its existence is not widely known by the public. The Abdimas Team from STSRD VISI, as a community service project supervised by the research and community service department of STSRD VISI (LP2M) was then assigned to help in promoting the potential of Dewi Rawe through the Tourism Village branding design program. The community service program is using the model of designing methodology. The results of the program are the maps of the tourism villages, the promotion poster, the village sign system, the booklet design, and the calendar design of 2020. The five types of the media are then presented and contributed directly to the tourism village in a design workshop event.